Genetic patterning for child psychopathology is distinct from that for adults and implicates fetal cerebellar development - Hughes, Dylan E.; Kunitoki, Keiko; Elyounssi, Safia; Luo, Mannan; Bazer, Oren M.; Hopkinson, Casey E.; Dowling, Kevin F.; Doyle, Alysa E.; Dunn, Erin C.; Eryilmaz, Hamdi; Gilman, Jodi M.; Holt, Daphne J.; et al. (Nature neuroscience, 2023)
Childhood psychiatric symptoms are often diffuse but can coalesce into discrete mental illnesses during late adolescence. We leveraged polygenic scores (PGSs) to parse genomic risk for childhood symptoms and to uncover related neurodevelopmental mechanisms with transcriptomic and neuroimaging data. In independent samples (Adolescent Brain Cognitive Development, Generation R) a narrow cross-disorder neurodevelopmental PGS, reflecting risk for attention deficit hyperactivity disorder, autism, depression and Tourette syndrome, predicted psychiatric symptoms through early adolescence with greater sensitivity than broad cross-disorder PGSs reflecting shared risk across eight psychiatric disorders, the disorder-specific PGS individually or two other narrow cross-disorder (Compulsive, Mood-Psychotic) scores. Neurodevelopmental PGS-associated genes were preferentially expressed in the cerebellum, where their expression peaked prenatally. Further, lower gray matter volumes in cerebellum and functionally coupled cortical regions associated with psychiatric symptoms in mid-childhood. These findings demonstrate that the genetic underpinnings of pediatric psychiatric symptoms differ from those of adult illness, and implicate fetal cerebellar developmental processes that endure through childhood. The authors associate a novel genomic risk score with a broad set of psychiatric symptoms in children. They trace the impact of associated genes on cerebellar developmental processes that originate in fetal life and endure through early adolescence.